(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2022)
By the end of 2021, it has been almost two years that schools in various parts of the world have not been able to carry out face-to-face learning activities due to the Covid-19 pandemic. In this situation, online learning is considered to be the best solution so that learning activities can continue. However, the continuous implementation of online learning for a long time has resulted in learning loss – the condition of decreasing students’ abilities and skills in cognitive, affective, and psychomotor aspects. To prevent the exacerbation of learning loss conditions, educators must continue working together to innovate in utilizing technology in learning activities. The use of digital technology is useful to control the implementation of learning and education management, especially after the emergence of COVID-19. That way technology becomes the most important part in helping the online learning process.